A novel superabsorbent from raw corn straw and poly(acrylic acid). Issue 7 (25th July 2015) - Jin, Shuping; Chen, Jun; Mao, Jianying; Yue, Guoren; Han, Yuqi; Yu, Xinghai
Abstract : A superabsorbent (CS/PAA SAR) for agriculture based on raw corn straw was prepared by free radical polymerization of acrylic acid (AA) in the presence of corn straw (CS) powder, which was used as received without any treatments. The water absorbency (WA) of SAR was investigated. The results show that SAR possesses a maximum WA of 663 g/g in distilled water and 61 g/g in 0.9 wt% NaCl solution. The structure of SAR was studied by Fourier transforms infrared spectroscopy, scanning electron microscopy, X‐ray diffraction, and differential scanning calorimeter, respectively. And the results indicate that the CS/PAA SAR possesses an interconnecting polymer network and sea‐island type phase separated structure, and the crystallinity decreases compared with the native cellulose because of the decreased content of CS. POLYM. COMPOS., 38:1353–1362, 2017. © 2015 Society of Plastics Engineers